2018
DOI: 10.1590/0004-282x20180062
|View full text |Cite|
|
Sign up to set email alerts
|

Brazilian consensus on Duchenne muscular dystrophy. Part 2: rehabilitation and systemic care

Abstract: Significant advances in the understanding and management of Duchenne muscular dystrophy (DMD) have occurred since the publication of international guidelines for DMD care in 2010. Our objective was to provide an evidence-based national consensus statement for multidisciplinary care of DMD in Brazil. A combination of the Delphi technique with a systematic review of studies from 2010 to 2016 was employed to classify evidence levels and grade of recommendations for the guideline. Our recommendations were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 58 publications
0
22
0
9
Order By: Relevance
“…On the other hand, Almeida (1998) reported that the cutoff point for literate elderly is 23/24, consistent with normative guides from the original version of the test (Folstein et al, 1975). The MMSE has been recommended by the Brazillian DMD Consensus as a means of assessing cognitive performance among individuals with DMD (Araujo et al, 2018) DMD Staging (Vignos Scale). We used the DMD Vignos Scale (Vignos et al, 1963) to characterize the level of functionality of participants with muscular dystrophies.…”
Section: Assessment Measuresmentioning
confidence: 99%
“…On the other hand, Almeida (1998) reported that the cutoff point for literate elderly is 23/24, consistent with normative guides from the original version of the test (Folstein et al, 1975). The MMSE has been recommended by the Brazillian DMD Consensus as a means of assessing cognitive performance among individuals with DMD (Araujo et al, 2018) DMD Staging (Vignos Scale). We used the DMD Vignos Scale (Vignos et al, 1963) to characterize the level of functionality of participants with muscular dystrophies.…”
Section: Assessment Measuresmentioning
confidence: 99%
“…For the same reason, authors support the use of antibiotics in the presence of early pulmonary infection signs, like fever, hypoxemia, leukocytosis, high C-reactive protein levels, expectoration, or infiltrations on chest X-ray 16 . Brazilian consensus on Duchenne muscular dystrophy (2018) also emphasizes the need for an immunization regimen that includes 3 doses of Pneumococcal Conjugate Vaccine (Pn10 or Pn13), 1 dose of Pneumococcal Polysaccharide Vaccine (Pn23) and annual doses of Anti-Influenza Vaccine in children with DMD, particularly those using corticosteroids 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive aspect was assessed by applying the MMSE, which has been validated for the Brazilian population, 17 and was recommended by the Brazilian DMD Consensus to assess cognitive performance. 18 In our study, we set a minimum score of 10 points, this is the minimum grade for DMD patients to understand simple verbal commands. 16 The MMSE is a test designed to assess specific cognitive functions (temporal orientation, spatial orientation, memory, attention and calculation, three-word recall, language, and constructive visual capacity).…”
Section: Methodsmentioning
confidence: 99%